Elicitation of Operational Requirements in ATC Activities Automation Process: The TWR Case - Dirickson, Yuri Maximilian Rottner; Vismari, Lucio Flavio; Camargo, João Batista (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
Several countries have been investing in upgrading their air traffic management systems as a way to cope with the growing demand for this mode of transport. Among the major modernization projects are the NextGen (USA) and SESAR(Europe), which one of the main objectives is to increase the efficiency of the services provided by air traffic controllers(ATCo) by automating part of their tasks. However, one must ensure that automated tasks do not impact negatively on the air traffic performance and safety. Thus, this paper presents a study of ATCo operational requirements elicitation to be considered in the process of automation. Due to aerodrome regions present the greatest historical number of accidents compared to other flight regions, the aerodrome control service (TWR) was adopted as acase study. The Enhanced Function Flow Block Diagram was the method adopted for the functional analysis of this study.